New catalytic reactions using sulfur dioxide - Willis, M (Taylor and Francis, 2019)
The sulfur dioxide surrogate DABSO is employed in a series of metal-catalyzed transformations to access useful sulfonyl-derived functional groups, such as sulfones, sulfonamides and sulfinate salts. Both palladium and copper catalyzed reactions are described. This work was presented at the 28th International Symposium on the Organic Chemistry of Sulfur, held in Tokyo in the summer of 2018.